War, Media, and Propaganda: A Global Perspective - Kamalipour, Yahya R.; Snow, Nancy (Rowman & Littlefield Publishers, 2004)
This timely book presents a multifaceted look at war, media, and propaganda from international perspectives. Focusing on the media's role in global conflicts, prominent authors, journalists, scholars, and researchers provide an insightful overview of the impact of globalization on media practices. They examine the processes behind media coverage of war, sophisticated propaganda techniques, the dynamics of public opinion, and the effects on human affairs and communication. As the book moves through theoretical discussions to regional and national views, it explores cultural-political implications for the United States and other countries around the world, concluding with recommendations and solutions to key problems of media globalization.